Kinetic and equilibrium studies of adsorption of Pb(II) on low cost agri-waste adsorbent Jute Stick Powder - Alam, Jahangir; Uddin, Mohammad Nasir (European Journal of Chemistry, 2019)
A lingo-cellulosic material Jute Stick Powder was used as a biosorbent to remove Pb(II) ions from aqueous solution and the biosorption behavior was investigated as a function of pH, metal ion concentration, adsorbent dosages and agitation time. Sorption binding sites present in JSP was assessed by Infrared spectroscopy (IR) and Scanning Electron Micrograph (SEM). The determined experimental data were fitted to some common kinetic and equilibrium models. Langmuir isotherm and pseudo-second-order kinetic model gave better fit to experimental data. The study revealed that spontaneous ion-exchange and complexation process involved in the adsorption mechanism. When the repeated adsorption-desorption cycles were performed, JSP kept its adsorptive efficiency even after three cycles of reuse.